Current Status of Loop-Mediated Isothermal Amplification Technologies for the Detection of Honey Bee Pathogens - Cameron, Timothy C.; Wiles, Danielle; Beddoe, Travis (Frontiers in Veterinary Science, 2021)
Approximately one-third of the typical human Western diet depends upon pollination for production, and honey bees (Apis mellifera) are the primary pollinators of numerous food crops, including fruits, nuts, vegetables, and oilseeds. Regional large scale losses of managed honey bee populations have increased significantly during the last decade. In particular, asymptomatic infection of honey bees with viruses and bacterial pathogens are quite common, and co-pathogenic interaction with other pathogens have led to more severe and frequent colony losses. Other multiple environmental stress factors, including agrochemical exposure, lack of quality forage, and reduced habitat, have all contributed to the considerable negative impact upon bee health. The ability to accurately diagnose diseases early could likely lead to better management and treatment strategies. While many molecular diagnostic tests such as real-time PCR and MALDI-TOF mass spectrometry have been developed to detect honey bee pathogens, they are not field-deployable and thus cannot support local apiary husbandry decision-making for disease control. Here we review the field-deployable technology termed loop-mediated isothermal amplification (LAMP) and its application to diagnose honey bee infections.